Biografía : Joao Vilanova Artigas (2010)
Breve reseña del proceso de formación académica y la producción del arquitecto brasilero.
Keywords: ARTIGAS, JOAO BATISTA VILANOVA; BRASIL; ARQUITECTURA; MOVIMIENTO MODERNO; HISTORIA; BIOGRAFIAS